KUALITAS FISIK, KADAR AIR, DAN SEBARAN JAMUR PADA WAFER LIMBAH PERTANIAN DENGAN LAMA SIMPAN BERBEDA - Hermawan ,; Rudy Sutrisna; Muhtarudin . (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this research was to determine physical qualities, water content, and mould distribution  in wafer of agricultural waste with different storage time. The experimental design that used in this research is Randomized Complete Design (CRD) with four treatments and four replications.   Agricultural waste wafer consists of four treatments and four replications, namely R0: Wafer without being stored; R1: wafer were stored for two weeks; R2: Wafer were stored for four weeks; and R3: wafer were stored for six weeks.  The results of this research indicate that the wafer with differential storage was highly significant (P <0.01) for physical qualities, there are colour, and the scent of wafer.  The best treatment on wafer with differential storage was wafer that stored for four weeks.